Дискусійність та вичерпаність постмодерністського проекту - Поліщук, Я.О. (Слово і Час, 2019)
Предметом рефлексії автора статті є вичерпаність постмодернізму – філософської доктрини й
естетичної практики. У контексті сучасної української культури, що важко виходить із колоніальної
залежності, постмодернізм не став універсальним явищем. Він з'явився в 1986 – 1991 рр. як
відповідь на популярний на Заході світогляд. Згасання постмодернізму автор пов'язує з подіями
2013 – 2014 рр., коли українська культура й суспільство перейшли в нову фазу існування.
Українські інтелектуали вдаються до критики постмодернізму (Т. Гундорова, О. Забужко).
Література повертає собі авторитет як суспільно заангажована інституція. The main subject of the research in the present article is exhaustion of Postmodernism as a
philosophical doctrine and aesthetical practice. Postmodernism failed to become a generally accepted
phenomenon in the contemporary Ukrainian literature, which experiences a difficult process of getting
out from the colonial dependence. It appeared in Ukraine in 1986–1991 as an answer to the outlook
that was popular in the West. The author associates the end of this artistic trend with the events that
took place in 2013–2014, when Ukrainian society and Ukrainian culture moved into a new phase
of existence. The consequences of these events, reflected in the media, in public opinion and also
in literature lead to rejection of the postmodern postulates. The author states that these postulates
reveal a clear dysfunction. Postmodern play and general skepticism, as it turned out, not only may
show the position of an independent intellectual person, but also be an imitation strategy that conceals
a neo-imperial doctrine shown as a liberal project. Sometimes it’s too difficult to distinguish one
manifestation from another.
Thus, the author defines the boundaries of postmodernism clearly, showing the crash of its basic
principles. In the course of time this phenomenon got quite different interpretation, that’s why the
whole project now needs a systemic reset. From such point of view, the thesis about the death of
postmodernism has its reasons especially in the East of Europe. In the Ukrainian case it looks like a
real perspective due to characteristic intersection of time and place (the East of Europe) and puts the
western project of postmodernism into a dead end, prompting us to search for alternative worldview
and aesthetic models. However, this artistic trend can motivate a modern Ukrainian intellectual in a
special way, opening new horizons of comprehending his own epoch.